LINKING RESTAURANT QUALITY TO PERCEIVED COMPETITIVENESS: EVIDENCE FROM TRADITIONAL AND FAST FOOD RESTAURANTS IN INDONESIA - Sari, Regia Indah Kemala; Hanani, Nuhfil; Asmara, Rosihan; Wahyuningtyas , Agustina Shinta Hartati (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
The Indonesian restaurant industry faces increased competition between traditional and fast food outlets, making it essential to understand quality attributes influencing customer satisfaction and competitiveness. While studies focused on service quality, price, and digital presence, few compared these factors across restaurant types. This study examines the effects of food quality, employee service, physical environment, price, and digital presence on satisfaction and perceived competitiveness, with satisfaction as a mediator. Survey data from 239 respondents in Padang City, including 127 traditional and 112 fast food customers, were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Multigroup Analysis (MGA). Results show food quality and price significantly enhance satisfaction in both traditional (β = 0.379, p = 0.001; β = 0.227, p = 0.015) and fast food restaurants (β = 0.347, p = 0.001; β = 0.476, p < 0.001). Employee service quality (β = 0.304, p = 0.002) and physical environment (β = 0.220, p = 0.009) enhance competitiveness in traditional restaurants, whereas satisfaction (β = 0.575, p < 0.001) and digital presence (β = 0.628, p < 0.001) prevail in fast food outlets. Satisfaction mediates the relationship between food quality, price, and physical environment with competitiveness, especially in fast food. MGA confirms that competitiveness in traditional restaurants is driven by employee service, whereas in fast food, it is shaped by digital presence and satisfaction. This study offers insights by comparing restaurant formats in a developing market; however, its cross-sectional, single-city design limits generalizability, suggesting future studies expand regions and adopt longitudinal approaches. JEL Classification Codes: O32, M31, L83.